Henry Abramson, Torah from the Years of Wrath 1939–1943: The Historical Context of the Aish Kodesh. (25th January 2019) - Banasik, Benjamin
Abstract : Henry Abramson, Torah from the Years of Wrath 1939–1943: The Historical Context of the Aish Kodesh. S.l.: CreateSpace Independent Publishing Platform, 2017, pp. 294, ISBN: 9781975983727 (pbk).